(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
This article examines the theoretical and practical essence of pedagogical technologies and lesson modules in the context of modern education. It explores the evolution of pedagogical technology, its defining features, classifications, and its importance in improving teaching effectiveness and learners’ personal development. The study also highlights the experience of Uzbekistan in implementing innovative pedagogical technologies within the national education system.